The relationship between body composition before a sports fight and the technical and tactical performance of kickboxing athletes - Niewczas, M.; Wasacz, W.; Ambrozy, T.; Kucia, K.; Rydzik, L. (Archives of Budo Science of Martial Arts and Extreme Sports, 2023)
Background & Study Aim: Combat sports determined by weight categories require specialized analysis of the body composition of athletes. The purpose of this study is both to broaden knowledge about the overall and segmental body components of kickboxing athletes immediately before a sport fight, and that relationship of this indicators with technical-tactical performance.